Faktor-Faktor yang Berhubungan dengan Kejadian ISPA pada Balita - Berta Afriani (LPPM STIKES Al-Ma'arif Baturaja, 2020)
ISPA in infants is the main cause of infant mortality in the world. Mortality survey conducted by Subdit in 2013 places ISPA as the biggest cause of under-five mortality in Indonesia with a percentage of 32.10% of all under-five deaths. The purpose of this study is to determine the factors associated with ISPA in infants. This research method uses a cross sectional research design. The population in this study is the total number of children under five in the village like to move OKU Regency, the sample size is 144 children under five. Chi-square statistical test results obtained p value 0,000 between the use of mosquito coils, smoking behavior, occupancy density with ISPA events in infants, and p value 0.001 kitchen smoke ventilation with ISPA events in infants. There is a significant relationship between the use of mosquito coils, smoking behavior, kitchen smoke ventilation, occupancy density.